Thermo-Diffusion and Diffusion-Thermo Effects on MHD Free Convective Heat and Mass Transfer from a Sphere Embedded in a Non-Darcian Porous Medium. (30th August 2012) - Vasu, B.; Prasad, V. R.; Bég, O. Anwar
Abstract : The problem of combined heat and mass transfer by natural convection over a sphere in a homogenous non-Darcian porous medium subjected to uniform magnetic field is numerically studied, taking Soret/Dufour effects into account. The coupled, steady, and laminar partial differential conservation equations of mass, momentum, energy, and species diffusion are normalized with appropriate transformations. The resulting well-posed two-point boundary value problem is solved using the well-tested, extensively validated Keller-Box implicit finite difference method, with physically realistic boundary conditions. A parametric study of the influence of Soret number (Sr), Dufour number (Du), Forchheimer parameter (Λ), Darcy parameter (Da), buoyancy ratio parameter (N ), Prandtl number (Pr), Schmidt number (Sc), magnetohydrodynamic body force parameter (M ), wall transpiration (f w ) is the blowing/suction parameter, and streamwise variable ( ξ ) on velocity, temperature, and concentration function evolution in the boundary layer regime is presented. Shear stress, Nusselt number, and Sherwood number distributions are also computed. Applications of the study arise in hydromagnetic flow control of conducting transport in packed beds, magnetic materials processing, geophysical energy systems, and magnetohydrodynamic chromatography technology.